Evaluasi Gangguan Jaringan Distribusi Tegangan Menengah Menggunakan Failure Mode and Effect Analysis (FMEA) - Kholifah Yusuf Mubarok; Musa Partahi Marbun (TIN: Terapan Informatika Nusantara, 2026)
Disturbances in the medium voltage distribution network at PT PLN Persero UP3 Makassar Selatan cause repeated outages that disrupt supply continuity in a major economic hub of Eastern Indonesia, with 1,207 incidents recorded in 2024 dominated by the rainy season. This study aims to quantify unserved energy losses for each disturbance type, determine the severity and occurrence levels of failure modes, apply Failure Mode and Effect Analysis (FMEA) for risk mapping, and formulate preventive mitigation strategies. Historical outage data from 2024 and expert judgements from distribution maintenance personnel are processed through three‑phase power and Energy Not Supplied (ENS) calculations, severity–occurrence scaling, FMEA tabulation, and a 5×5 risk matrix to classify risk levels. The results show that lightning/extreme weather, trees/vegetation, animals, and “unidentified” causes generate the largest ENS and fall into the highest risk classes, while internal equipment failures generally remain at moderate to low risk. Recommended actions include reinforcing lightning protection and grounding, systematic vegetation management, installation of animal protection devices, improvement of joints and construction quality, optimization of protection operation, and community/social stakeholder outreach, which are estimated to be more cost‑effective than tolerating recurring outage losses.